2458. Disparities in Healthcare Providers' Interpretation and Implementation of ACIP's Meningococcal Vaccine Recommendations. (26th November 2018) - Huang, Liping; Goren, Amir; Lee, Lulu; Dempsey, Amanda; Srivastava, Amit
Abstract: Background: Serogroup B is the leading cause of invasive meningococcal disease (IMD) in United States. Among 16–23 year olds, particularly for college students, serogroup B (MenB) disease is greater than serogroups C, W, and Y combined. ACIP recommends routine immunization with MenACWY vaccine (Category A) but a non-routine recommendation based on individual clinical decision-making for MenB vaccine (Category B). Contrasting ACIP recommendations may affect how healthcare providers (HCP) prescribe meningococcal vaccines. We aimed to understand HCPs' decision process and vaccination practice pattern to prescribe meningococcal vaccines in relation to their experience and interpretations of ACIP recommendations. Methods: A web-based survey was conducted during August–October 2017 among a nationally representative HCP sample. Univariate analyses were conducted. Results: Of 529 HCP participants, 436 (82.4%) self-identified as prescribers of MenB only or both meningococcal vaccines, and 93 (17.6%) as prescribers of MenACWY vaccine only (Table 1). When HCPs were asked to rank the most impactful factor in their decision process, 45% ranked guideline considerations as the highest in their decisions to prescribe MenACWY to 16 year olds, followed by disease related factors (36%). For MenB vaccine, 40% ranked disease related factors as the highest, followed by guideline considerations (37%); however, contrasting to MenACWY vaccine (45% vs. 24%), there was no difference (37% vs. 38%) regarding how guideline considerations drove the decision to prescribe or not to prescribe MenBvaccine (Table 2). Overall, HCPs interpreted ACIP's MenACWY recommendation more uniformly than the MenB recommendation (Figure 1) with majority interpreting MenACWY vaccine as for everyone, whereas MenB was split into for everyone or for a sub-group based on risk factors; 1/4th of MenACWY only prescribers did not know how to interpret the MenB recommendation. Conclusion: The ACIP MenB vaccine recommendation is inconsistently interpreted across HCPs and might affect their decision process and vaccination practice pattern to prescribe meningococcal vaccines resulting in disparities in access to MenBvaccines. Disclosures: L. Huang, Pfizer: Employee and Shareholder, Salary and Stocks. A. Goren, Pfizer: Collaborator, Research support. L. Lee, Pfizer: Collaborator, Research support. A. Dempsey, Pfizer, Merck: Scientific Advisor, Consulting fee. A. Srivastava, Pfizer: Employee and Shareholder, Salary.